Ag-Mo / Ag film with high ductility and fatigue resistance and preparation method
By introducing a microalloyed Ag-Mo layer with high density nanotwins on the surface of the elemental Ag, a double-layer structure of Ag-Mo/Ag film is formed, which solves the problem that metal film conductors are prone to fatigue damage under cyclic loads, and achieves the effects of high ductility and fatigue resistance.
Patent Information
- Application Number
- CN202411654451.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-19
AI Technical Summary
Existing metal thin film conductors are prone to abnormal grain growth, surface extrusion or fatigue cracks under cyclic loads, resulting in a decrease in conductivity and affecting the functionality of flexible electronic devices.
Through cosputtering technology, a microalloyed Ag-Mo layer of high-density nanotwins is introduced on the surface of elemental Ag, forming a bilayer structure of Ag-Mo/Ag film, combining the fatigue resistance of nanotwins and the ductility of microalloys.
Ag-Mo/Ag film with high ductility and fatigue resistance is achieved, avoiding the adverse effects of reduced ductility caused by the introduction of alloy elements. At the same time, the anti-fatigue advantages of nanotwins are fully utilized, and the fatigue life of the film is significantly improved.
Smart Images

Figure CN119506805A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material surface modification, in particular to an Ag-Mo / Ag film with high ductility and fatigue resistance and a preparation method thereof. Background Art
[0002] With the advancement of materials science and advanced manufacturing technology, flexible electronic technology has been widely used in wearable devices, consumer electronics, human-computer interaction, energy and other fields. Face-centered cubic (FCC) metal films such as gold, copper and silver are often used as flexible conductors or electrode materials due to their high conductivity and good mechanical flexibility. Metal films at the micro-nano scale often have nanocrystalline polycrystalline structures. During the use of electronic devices, metal film conductors will be subjected to cyclic loads such as stretching and bending. Metal films are prone to abnormal grain growth, causing damage such as surface extrusion or fatigue cracks, resulting in a decrease in the conductivity of the metal film and affecting the functionality of the device. Therefore, the development of metal film conductors with excellent fatigue resistance is crucial to the development and application of flexible electronic technology.
[0003] Studies have shown that the introduction of high-density, uniformly oriented nanotwins through microalloying can significantly improve the fatigue resistance of FCC metals. However, the introduction of alloying elements and high-density nanotwins often leads to a significant decrease in the ductility of metal films. How to design the microstructure / structure of metal films to achieve both high ductility and high fatigue resistance is still a difficult problem that restricts the development of metal film conductors. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a Ag-Mo / Ag film with high ductility and fatigue resistance and a preparation method thereof, wherein a micro-alloyed Ag-Mo layer with high density nano-twins is introduced on the surface of single Ag by co-sputtering. The film not only avoids the adverse effect of reduced ductility caused by the introduction of alloy elements, but also gives full play to the fatigue resistance advantage of nano-twins.
[0005] The present invention is achieved through the following technical solutions: A high ductility and fatigue resistance Ag-Mo / Ag film, comprising a single-substance Ag layer and a micro-alloyed Ag-Mo layer, wherein the micro-alloyed Ag-Mo layer is attached to the surface of the single-substance Ag layer; the thickness ratio of the micro-alloyed Ag-Mo layer to the single-substance Ag layer is (1:9)-(1:1); The grain morphology of the single-substance Ag layer and the micro-alloyed Ag-Mo layer is columnar crystals, wherein the columnar crystals of the single-substance Ag layer contain 30-40% of twinned grains, and the columnar crystals of the Ag-Mo layer contain 100% of twinned grains.
[0006] Preferably, the microalloyed Ag-Mo layer has, by atomic content percentage, 97-99% Ag and 1-3% Mo.
[0007] Preferably, the interlayer spacing of the twin crystalline sheets in the single-substance Ag layer is about 35 nm; and the interlayer spacing of the twin crystalline sheets in the Ag-Mo layer is about 3 nm.
[0008] Preferably, the conductivity of the Ag-Mo / Ag film is up to 3.0×10 7 S m −1 .
[0009] A method for preparing a Ag-Mo / Ag film with high ductility and fatigue resistance comprises the following steps: In a vacuum environment, a single Ag layer and a micro-alloyed Ag-Mo layer are sequentially deposited on a substrate by a DC magnetron sputtering process, and then cooled to room temperature to obtain an Ag-Mo / Ag film.
[0010] The single-substance Ag layer is deposited by using an Ag target, and the alloyed Ag-Mo layer is deposited by co-sputtering of an Ag target and a Mo target.
[0011] Preferably, when sputtering a single-element Ag layer, the sputtering power of the Ag target is 120 W; when sputtering a micro-alloyed Ag-Mo layer, the sputtering power of the Ag target is 150 W, and the sputtering power of the Mo target is 20 W.
[0012] Preferably, during the DC magnetron sputtering process, the argon gas pressure is 0.5 Pa and the substrate rotation speed is fixed at 10 r / min.
[0013] Preferably, when sputtering a single Ag layer, the deposition rate is 0.36 nm / s; when sputtering a microalloyed Ag-Mo layer, the deposition rate is 0.45 nm / s.
[0014] Preferably, the deposition time of the single-substance Ag layer is 1390-2500 s.
[0015] Preferably, the deposition time of the alloyed Ag-Mo layer is 223-1112 s.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The present application provides a Ag-Mo / Ag film with high ductility and fatigue resistance, which is a double-layer structure metal film of elemental Ag and micro-alloyed Ag-Mo. High-density aligned nano twins are introduced into the surface Ag film by Mo micro-alloying, and high ductility and high fatigue resistance are achieved at the same time. Due to the low content of micro-alloy elements, low electron scattering effect of twin boundaries and unique double-layer structure design, the film has conductivity and ductility comparable to that of Ag film. In addition, due to the introduction of high-density nano twins and the compatible plastic deformation ability between micro-alloyed Ag-Mo and elemental Ag, fatigue extrusion on the film surface can be effectively suppressed, fatigue crack initiation is delayed and crack propagation is hindered, and fatigue life is greatly improved. The film not only avoids the adverse effects of reduced ductility caused by the introduction of alloying elements, but also gives full play to the anti-fatigue advantages of nano twins.
[0017] The present application provides a method for preparing a Ag-Mo / Ag film with high ductility and fatigue resistance. The single substance Ag is subjected to Mo microalloying treatment by co-sputtering, high-density nanotwins are introduced, and the adverse effect of the introduction of nanotwins on the ductility of the film is reduced by the double-layer structure design of single substance Ag and microalloyed Ag-Mo. A uniform and dense Ag-Mo / Ag film with strong film-base bonding and high ductility and fatigue resistance is successfully prepared by DC magnetron sputtering deposition process. Thanks to the introduction of high-density nanotwins and the unique double-layer structure design, the Ag-Mo / Ag film not only maintains high conductivity and ductility, but also due to the intrinsic high fatigue resistance of nanotwins and the compatible plastic deformation ability between the microalloyed Ag-Mo layer and the single substance Ag layer, the formation and expansion of film fatigue damage are effectively suppressed, and fatigue resistance is significantly improved. The preparation method of the Ag-Mo / Ag film is simple, cost-effective, and suitable for large-scale production. The application of this film is expected to significantly improve the performance and reliability of flexible electronic devices, opening up new possibilities for the development of flexible electronic technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 This is the X-ray diffraction pattern of the metal film of the present invention.
[0020] Figure 2 The planar transmission electron microscope (TEM) photograph and the corresponding selected electron diffraction pattern (SADP) of the Ag-Mo single-layer film of the comparative example of the present invention are shown.
[0021] Figure 3 The transmission electron microscope (TEM) cross-sectional photographs of the thin films of various embodiments and comparative examples of the present invention are shown in FIG.
[0022] Figure 4 It is a statistical diagram of cracking strain of the Ag-Mo / Ag film of the present invention.
[0023] Figure 5 This is a fatigue life curve of the Ag-Mo / Ag film of the present invention. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0025] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0026] A high ductility and fatigue resistance Ag-Mo / Ag film, comprising a single-substance Ag layer and a micro-alloyed Ag-Mo layer, wherein the micro-alloyed Ag-Mo layer is attached to the surface of the single-substance Ag layer; the thickness ratio of the micro-alloyed Ag-Mo layer to the single-substance Ag layer is (1:9)-(1:1). The micro-alloyed Ag-Mo layer, in terms of atomic content percentage, contains 97-99% Ag and 1-3% Mo.
[0027] The single-substance Ag layer has a columnar grain morphology, in which twinned grains account for 30%-40% of the columnar crystals, and the interlayer spacing of the twinned grains is about 35 nm; The grain morphology of the microalloyed Ag-Mo layer of the Ag-Mo / Ag film is also columnar crystals, in which the proportion of twinned grains in the columnar crystals is 100%, and the interlayer spacing of the twinned grains is about 3 nm.
[0028] The total thickness of the highly ductile and fatigue-resistant Ag-Mo / Ag film is 1000 nm, and it consists of two layers: a single Ag layer and a micro-alloyed Ag-Mo layer, wherein the micro-alloyed Ag-Mo layer is a surface layer deposited on the surface of the single Ag layer. Under tensile conditions, the film cracking strain is 2-6 times higher than that of the single-layer Ag-Mo film; by reasonably optimizing the thickness ratio of the micro-alloyed Ag-Mo layer, the fatigue life of the film can be increased by more than 4 times compared with the single-layer Ag film at a fatigue strain amplitude of 1%.
[0029] The Ag-Mo / Ag film of the present application, the high-density nano twins inside the micro-alloyed Ag-Mo layer can adapt to ductile deformation by activating cross-twin dislocations under cyclic loads, effectively suppressing stress concentration and delaying the initiation of fatigue cracks, so that the surface micro-alloyed Ag-Mo layer exhibits high inherent fatigue resistance. In addition, since the single-substance Ag layer and the micro-alloyed Ag-Mo layer have similar lattice constants and elastic moduli, the Ag / Ag-Mo interface exhibits excellent deformation compatibility under cyclic loading, and dislocations are easy to coordinate the deformation on both sides through the interface, thereby suppressing the formation of interface damage. In addition, the presence of the surface micro-alloyed Ag-Mo layer effectively suppresses the fatigue extrusion of the lower single-substance Ag layer and delays the initiation of fatigue cracks. At the same time, the fatigue damage on the surface is distributed in a reticular manner, indicating that the propagation of fatigue damage in the plane is hindered, which helps to consume plastic deformation energy and avoid the destruction of the film conductive path, thereby ensuring that the change of the film resistance is maintained at a relatively low level. The Ag-Mo / Ag film has ultra-high electrical conductivity and excellent fatigue resistance. The conductivity of the film is as high as 3.0×10 7 S m −1 The unique double-layer structure design gives the film excellent fatigue resistance.
[0030] The corresponding application also provides a method for preparing the above-mentioned Ag-Mo / Ag film with high ductility and fatigue resistance, comprising the following process: In a vacuum environment, a single Ag layer and a micro-alloyed Ag-Mo layer are sequentially deposited on a substrate by a DC magnetron sputtering process, and then cooled to room temperature to obtain an Ag-Mo / Ag film.
[0031] The single-substance Ag layer is deposited by using a single Ag target, and the alloyed Ag-Mo layer is deposited by using a co-sputtering of an Ag target and a Mo target.
[0032] When sputtering a single Ag layer, the sputtering power of the Ag target is 120 W; when sputtering a microalloyed Ag-Mo layer, the sputtering power of the Ag target is 150 W, and the sputtering power of the Mo target is 20 W. During the deposition process, the argon gas pressure is 0.5 Pa, and the substrate rotation speed is fixed at 10 r / min.
[0033] During the preparation process, the substrate is first cleaned and dried, then vacuum etched, and then pre-sputtered for a certain period of time on the etched substrate, and finally formal DC magnetron sputtering is performed.
[0034] In some embodiments, the substrate is ultrasonically cleaned with anhydrous ethanol for 15 minutes. After cleaning, the substrate is dried with a hair dryer to remove dust and oil on the surface of the substrate.
[0035] In some embodiments, the substrate is etched in a vacuum coating chamber using Ar + Ion etching further removes impurities on the substrate, Ar + The etching power was 200 W, the etching pressure was 0.5 Pa, and the etching time was 5 min.
[0036] In some embodiments, pre-sputtering is performed for 30 s before formal sputtering deposition. Before the pre-sputtering, the argon gas ventilation time is 30 s with a gas flow rate of 40 sccm to remove adsorbed substances on the surface of the target material.
[0037] The Ag-Mo / Ag film provided in this application combines magnetron sputtering single target sputtering with dual target co-sputtering deposition technology, and ensures the uniformity and density of the film by precisely setting the sputtering parameters. Before formal deposition, the substrate surface is strictly cleaned and pretreated to ensure good bonding between the film and the substrate. During the deposition process, the substrate rotates at a constant speed of 10 r / min to ensure uniform deposition of the film. Finally, the film is naturally cooled to room temperature in a high vacuum environment to ensure the uniformity of the film's structure and minimization of defects.
[0038] Example 1 A method for preparing a Ag-Mo / Ag film with high ductility and fatigue resistance comprises the following steps: Step 1: ultrasonically clean the polyimide substrate in anhydrous ethanol for 15 min and then quickly dry it to make the surface of the polyimide substrate clean and tidy.
[0039] Step 2: Fix the cleaned polyimide substrate on the base plate and put it into the coating chamber, and then draw the vacuum degree of the back to 4×10 -4 Pa to further clean the polyimide substrate, the etching power was 200 W, the etching pressure was 0.5 Pa, and the time was 5 min.
[0040] Step 3: Pre-sputter the Ag target and Mo target of magnetron sputtering, introduce argon gas for 30 seconds to reach and stabilize the working gas pressure, and pre-sputter the target material for 30 seconds.
[0041] Step 4: Prepare Ag-Mo / Ag thin film on the substrate by using DC magnetron sputtering process.
[0042] Firstly, a high-purity Ag target (purity of 99.995 wt.%) was used for DC magnetron sputtering with a sputtering power of 120 W, a substrate rotation speed of 10 r / min, a deposition gas pressure of 0.5 Pa, an argon gas flow rate of 40 sccm, and a deposition rate of 0.36 nm / s for 1390 s at room temperature to obtain a 500 nm thick single-element Ag layer.
[0043] Then, a micro-alloyed Ag-Mo film was deposited on the single Ag layer by DC co-sputtering using an Ag target (purity of 99.995 wt.%) and a Mo target (purity of 99.95 wt.%). The target sputtering powers were 150 W and 20 W, respectively, the substrate rotation speed was 10 r / min, the deposition gas pressure was set to 0.5 Pa, the argon gas flow rate was 40 sccm, and the deposition time was 1112 s at a deposition rate of 0.45 nm / s at room temperature to obtain a micro-alloyed Ag-Mo layer with a thickness of 500 nm.
[0044] Step 4: After the sample is naturally cooled to room temperature in the vacuum coating chamber for 1 hour, it is taken out to obtain an Ag-Mo / Ag film with a thickness of about 1000 nm.
[0045] The thickness of the single Ag layer and the microalloyed Ag-Mo layer in the Ag-Mo / Ag film is 500 nm, and the sample is named Ag-Mo500 / Ag500. The microstructure of the prepared Ag-Mo / Ag film was characterized. The results showed that the single Ag layer grains showed a columnar crystal structure, in which the proportion of twinned grains was relatively small, and the microalloyed Ag-Mo layer grains also showed a columnar crystal structure, in which the proportion of twinned grains was 100%, and the interlayer spacing of the twinned grains was extremely small, about 3 nm. The film showed obvious double-layer structural characteristics in the thickness direction.
[0046] Example 2 A method for preparing a Ag-Mo / Ag film with high ductility and fatigue resistance comprises the following steps: Step 1: ultrasonically clean the polyimide substrate in anhydrous ethanol for 15 min and then quickly dry it to make the surface of the polyimide substrate clean and tidy.
[0047] Step 2: Fix the cleaned polyimide substrate on the base plate and put it into the coating chamber, and then draw the vacuum degree of the back to 4×10 -4 Pa to further clean the polyimide substrate, the etching power was 200 W, the etching pressure was 0.5 Pa, and the time was 5 min.
[0048] Step 3: Pre-sputter the Ag target and Mo target of magnetron sputtering, introduce argon gas for 30 seconds to reach and stabilize the working gas pressure, and pre-sputter the target material for 30 seconds.
[0049] Step 4: Prepare Ag-Mo / Ag thin film on the substrate by using DC magnetron sputtering process.
[0050] Firstly, a high-purity Ag target (purity of 99.995 wt.%) was used for DC magnetron sputtering with a sputtering power of 120 W, a substrate rotation speed of 10 r / min, a deposition gas pressure of 0.5 Pa, an argon gas flow rate of 40 sccm, and a deposition rate of 0.36 nm / s for 2223 s at room temperature to obtain a single Ag layer with a thickness of 800 nm.
[0051] Then, a micro-alloyed Ag-Mo film was deposited on the single Ag layer by DC co-sputtering using an Ag target (purity of 99.995 wt.%) and a Mo target (purity of 99.95 wt.%). The target sputtering powers were 150 W and 20 W, respectively, the substrate rotation speed was 10 r / min, the deposition gas pressure was set to 0.5 Pa, the argon gas flow rate was 40 sccm, and the deposition was carried out at a deposition rate of 0.45 nm / s for 445 s at room temperature to obtain a micro-alloyed Ag-Mo layer with a thickness of 200 nm.
[0052] Step 4: After the sample is naturally cooled to room temperature in the vacuum coating chamber for 1 hour, it is taken out to obtain a Ag-Mo / Ag film with a thickness of about 1000 nm, wherein the thickness of the single Ag layer and the microalloyed Ag-Mo layer are 800 nm and 200 nm respectively, and the sample is named Ag-Mo200 / Ag800.
[0053] The prepared Ag-Mo / Ag film was characterized by microstructure. The results showed that the single-element Ag layer had a columnar crystal structure, in which the twinned grains accounted for a relatively small proportion. The microalloyed Ag-Mo layer also had a columnar crystal structure, in which the twinned grains accounted for 100%, and the interlayer spacing of the twinned grains was extremely small, about 3 nm. The film showed obvious double-layer structural characteristics in the thickness direction.
[0054] Example 3 A method for preparing a Ag-Mo / Ag film with high ductility and fatigue resistance comprises the following steps: Step 1: ultrasonically clean the polyimide substrate in anhydrous ethanol for 15 min and then quickly dry it to make the surface of the polyimide substrate clean and tidy.
[0055] Step 2: Fix the cleaned polyimide substrate on the base plate and put it into the coating chamber, and then draw the vacuum degree of the back to 4×10 -4Pa to further clean the polyimide substrate, the etching power was 200 W, the etching pressure was 0.5 Pa, and the time was 5 min.
[0056] Step 3: Pre-sputter the Ag target and Mo target of magnetron sputtering, introduce argon gas for 30 seconds to reach and stabilize the working gas pressure, and pre-sputter the target material for 30 seconds.
[0057] Step 4: Prepare Ag-Mo / Ag thin film on the substrate by using DC magnetron sputtering process.
[0058] Firstly, a high-purity Ag target (purity of 99.995 wt.%) was used for DC magnetron sputtering with a sputtering power of 120 W, a substrate rotation speed of 10 r / min, a deposition gas pressure of 0.5 Pa, an argon gas flow rate of 40 sccm, and a deposition rate of 0.36 nm / s for 2500 s at room temperature to obtain a single Ag layer with a thickness of ~ 900 nm.
[0059] Then, Ag target (purity of 99.995 wt.%) and Mo target (purity of 99.95 wt.%) were used for DC co-sputtering to deposit micro-alloyed Ag-Mo thin film on the single Ag layer. The target sputtering powers were 150 W and 20 W, respectively, the substrate rotation speed was 10 r / min, the deposition gas pressure was set to 0.5 Pa, the argon gas flow rate was 40 sccm, and the deposition was carried out at a deposition rate of 0.45 nm / s for 223 s at room temperature to obtain a micro-alloyed Ag-Mo layer with a thickness of 100 nm.
[0060] Step 4: After the sample is naturally cooled to room temperature in the vacuum coating chamber for 1 hour, it is taken out to obtain an Ag-Mo / Ag film with a thickness of about 1000 nm, wherein the thickness of the single Ag layer and the micro-alloyed Ag-Mo layer are 900 nm and 100 nm respectively, and the sample is named Ag-Mo100 / Ag900.
[0061] The prepared Ag-Mo / Ag film was characterized by microstructure. The results showed that the single-element Ag layer had a columnar crystal structure, in which the twinned grains accounted for a relatively small proportion. The microalloyed Ag-Mo layer also had a columnar crystal structure, in which the twinned grains accounted for 100%, and the interlayer spacing of the twinned grains was extremely small, about 3 nm. The film showed obvious double-layer structural characteristics in the thickness direction.
[0062] It should be noted that the total thickness of the Ag-Mo / Ag films prepared in the above Examples 1-3 is 1000 nm, which is only for exemplary purposes. Ag-Mo / Ag films of different thicknesses can be prepared by controlling the thickness ratio of the microalloyed Ag-Mo layer and the elemental Ag layer and adjusting the deposition time.
[0063] Comparative Example 1 The difference between this comparative example and Examples 1-3 is that no single Ag layer is added, and a single-layer micro-alloyed Ag-Mo film is used, wherein the thickness of the Ag-Mo layer is 1000 nm, and the film is named Ag-Mo. The rest of the method is the same as that of Examples 1-3.
[0064] Comparative Example 2 The difference between this comparative example and Example 1-3 is that there is no addition of surface microalloyed Ag-Mo film, and it is a single-layer single-substance Ag film, wherein the thickness of the single-substance Ag layer is 1000 nm, and the film is named Ag. The rest of the method is the same as that of Example 1-3.
[0065] Figure 1 The XRD experimental results of the metal films prepared in Examples 1-3 and Comparative Examples 1-2 are shown, explaining the significant (111) out-of-plane preferred orientation of the films. Figure 2 The planar TEM images of microalloyed Ag-Mo films prepared by DC magnetron dual-target co-sputtering and the corresponding SADP are shown, revealing the microstructural characteristics of the microalloyed Ag-Mo film nanocrystals. Figure 3 The cross-sectional TEM experimental results of the metal films prepared in Examples 1-2 and Comparative Example 1 are shown, revealing the double-layer structural characteristics of the single-element Ag layer and the micro-alloyed Ag-Mo layer in the thickness direction and the high-density nanotwin characteristics existing in the micro-alloyed Ag-Mo layer. Figure 4 The high crack strain of Ag-Mo / Ag film is demonstrated. Under uniaxial tension conditions, the crack strain of the film is 2-6 times higher than that of single-layer Ag-Mo film. Figure 5 The fatigue life of the Ag-Mo / Ag film is shown as a function of the thickness of the microalloyed Ag-Mo layer. The fatigue loading strain amplitude is 1%, and the loading mode is tension-tension fatigue. The test results show that the fatigue life of the film prepared by the present invention increases first and then decreases with the increase of the thickness of the surface microalloyed Ag-Mo layer. When the thickness of the surface microalloyed Ag-Mo layer is 200 nm, the fatigue life of the film reaches the best, and its fatigue life is increased by more than 4 times compared with the single Ag film.
[0066] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. An Ag-Mo / Ag film with high ductility and fatigue resistance, characterized in that: It comprises a single substance Ag layer and a micro-alloyed Ag-Mo layer, wherein the micro-alloyed Ag-Mo layer is attached to the surface of the single substance Ag layer; the thickness ratio of the micro-alloyed Ag-Mo layer to the single substance Ag layer is (1:9)-(1:1); The grain morphology of the single-substance Ag layer and the micro-alloyed Ag-Mo layer is columnar crystals, wherein the columnar crystals of the single-substance Ag layer contain 30-40% of twinned grains, and the columnar crystals of the Ag-Mo layer contain 100% of twinned grains.
2. The Ag-Mo / Ag film with high ductility and fatigue resistance according to claim 1, characterized in that: The micro-alloyed Ag-Mo layer has, by atomic content percentage, 97-99% Ag and 1-3% Mo.
3. The Ag-Mo / Ag film with high ductility and fatigue resistance according to claim 1, characterized in that: The interlayer spacing of the twin crystals in the single-substance Ag layer is about 35 nm; and the interlayer spacing of the twin crystals in the Ag-Mo layer is about 3 nm.
4. The Ag-Mo / Ag film with high ductility and fatigue resistance according to claim 1, characterized in that: The conductivity of the Ag-Mo / Ag film is up to 3.0×10 7 S m −1 .
5. A method for preparing a Ag-Mo / Ag thin film with high ductility and fatigue resistance according to any one of claims 1 to 4, characterized in that: The process includes: In a vacuum environment, a single Ag layer and a micro-alloyed Ag-Mo layer are sequentially deposited on a substrate by a DC magnetron sputtering process, and then cooled to room temperature to obtain an Ag-Mo / Ag film. The single-substance Ag layer is deposited by using an Ag target, and the alloyed Ag-Mo layer is deposited by co-sputtering of an Ag target and a Mo target.
6. The method for preparing a Ag-Mo / Ag thin film with high ductility and fatigue resistance according to claim 5, characterized in that: When sputtering a single Ag layer, the sputtering power of the Ag target is 120 W; when sputtering a micro-alloyed Ag-Mo layer, the sputtering power of the Ag target is 150 W, and the sputtering power of the Mo target is 20 W.
7. The method for preparing a Ag-Mo / Ag thin film with high ductility and fatigue resistance according to claim 5, characterized in that: During the DC magnetron sputtering process, the argon gas pressure was 0.5 Pa and the substrate rotation speed was fixed at 10 r / min.
8. The method for preparing a Ag-Mo / Ag thin film with high ductility and fatigue resistance according to claim 5, characterized in that: When sputtering a single Ag layer, the deposition rate is 0.36 nm / s; when sputtering a microalloyed Ag-Mo layer, the deposition rate is 0.45 nm / s.
9. The method for preparing a Ag-Mo / Ag thin film with high ductility and fatigue resistance according to claim 5, characterized in that: The deposition time of the single substance Ag layer is 1390-2500 s.
10. The method for preparing a Ag-Mo / Ag thin film with high ductility and fatigue resistance according to claim 5, characterized in that: The deposition time of the alloyed Ag-Mo layer is 223-1112 s.
Citation Information
Patent Citations
Ag-Cu-Al alloy film and preparation method thereof
CN117467939A
High-strength hot-dip galvanized steel sheet and hot-dip galvannealed steel sheet having fatigue resistance, corrosion resistance, ductility and plating adhesion, after severe deformation, and a metho
CN1639375A
Sputtering target material for forming thin film, thin film, electrode-wired layer, optical recording medium, electronic component, optoelectronic component and electronic device
JP2004238655A
Stable nanocrystalline metal alloy coatings with ultra-low wear
US10763000B1
Ag ALLOY SPUTTERING TARGET AND Ag ALLOY FILM MANUFACTURING METHOD
US20170191154A1